Experimental Determination of Polycrystalline Salt Rock Thermal Conductivity, Diffusivity and Specific Heat From 20 to 240°C - Ren, Yiwei; Yuan, Qiang; Kang, Yanfei; Wei, Like; Li, Zongze; Jiang, Deyi; He, Huayong; Xu, Hong (Frontiers in Earth Science, 2022)
Salt rock is recognized as one of the most suitable parent rocks for geological disposal of high level radioactive waste due to its low permeability, good ductility, good thermal conductivity and damage self-healing properties. The thermal conductivity of salt rock directly affects the temperature of disposal storage and surrounding rock, high temperature will lead to a series of problems such as nuclear waste storage tank rupture, mechanical and permeability reduction of surrounding rock. In this paper, the thermal conductivity, specific heat and thermal diffusion coefficient of NaCl single crystal made by crystallization method in the laboratory and polycrystalline salt rock from Khewra salt mine were measured in the range of 22–240°C by the transient plane source method. The results showed that the thermal conductivity and thermal diffusivity of salt rock decrease gradually with the increase of temperature, while the specific heat capacity increases with the increase of temperature. The thermal conductivity of salt rock is slightly lower than that of single-crystal NaCl. The reason for this phenomenon may be that there are a few pores in salt rock. Based on the experimental data, the models of thermal conductivity, thermal diffusivity and specific heat of salt rock with temperature were established. The results can provide a reference for the construction of underground salt rock high-level radioactive waste disposal repository. Based on the thermal conductivity model of polycrystalline salt rock established in this paper, the temperature field evolution during the operation of the underground salt rock high-level nuclear waste repository in 1,000 years was studied. It was found that the temperature of the glass solidified of high-level radioactive waste reached the highest (177.6°C) and then dropped rapidly. The decay heat radiation influence radius of the nuclear waste reaches its maximum in about 50 years of operation of the repository and then gradually decreases.